Improving Knowledge Is Not Enough: Multi-level Determinants of Maternal, Infant, and Young Child Nutrition Identified Through Formative Research in the Republic of Kiribati (P10-037-19) - Kodish, Stephen (Curr Dev Nutr, 2019)
OBJECTIVES: To elucidate the factors contributing to high childhood stunting, widespread micronutrient deficiencies, and maternal overweight/obesity in Kiribati METHODS: This two-phase formative research study had an emergent and iterative design using the socio-ecological model as the guiding theoretical framework. Phase 1 was exploratory and generated emergent themes; phase 2 was confirmatory and corroborated, clarified, and built off phase 1 findings. A triangulation of qualitative and ethnographic methods was used to collect data from diverse participant types. In phase 1, in-depth interviews, free lists, seasonal food availability calendar workshops, and household observations were conducted. In phase 2, focus groups, pile sorts, participatory workshops, and repeated observations were completed. Textual data were analyzed using nVivo; ethnographic data were analyzed using Anthropac for cultural domain analysis. RESULTS: Data were collected in both urban (Teaoraereke) and rural (Bitaritari), Kiribati from March – May, 2018. Fifty-six interviews, 11 focus groups, 10 participatory workshops, 84 free lists, 94 pile sorts, and 20 observations were conducted among caregivers, health workers/staff, community leaders, and households with young children under two years. Structural, social, and behavioral factors at multiple levels all contribute to the sub-optimal nutrition situation of Kiribati. At the policy level, the Kiribati food system relies heavily on imported, non-perishable foods which are non nutritious yet more available and accessible than locally-grown options. At the community level, longstanding social norms around food and illness, such as reliance on traditional medicine in the early days of life and food procriptions during pregnancy, are contributing factors. At the household and interpersonal levels, social activities such as kava drinking contribute to lower household incomes making food access more difficult. Individual perceptions toward handwashing and feeding during illness differentially affect dietary practices by caregiver. CONCLUSIONS: This research underscores the importance of addressing multiple levels of influence, not just focusing on individual-level factors such as knowledge, when intervening to improve nutrition in Kiribati and other similar Pacific Island Country contexts. FUNDING SOURCES: UNICEF.